2016
DOI: 10.3847/0004-637x/820/1/18
|View full text |Cite
|
Sign up to set email alerts
|

Isotropic at the Break? 3d Kinematics of Milky Way Halo Stars in the Foreground of M31

Abstract: We present the line-of-sight (LOS) velocities for 13 distant main sequence Milky Way halo stars with published proper motions (PMs). The PMs were measured using long baseline (5-7 years) multi-epoch Hubble Space Telescope/Advanced Camera for Surveys photometry, and the LOS velocities were extracted from deep (5-6 hr integrations) Keck II/DEIMOS spectra. We estimate the parameters of the velocity ellipsoid of the stellar halo using a Markov chain Monte Carlo ensembler sampler method. The velocity second moments… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 53 publications
2
36
2
Order By: Relevance
“…On the other hand, there is strong evidence to expect  b 0 for the Galactic stellar halo (Kafle et al 2014), and previous studies have shown that the velocity distribution of GCs in the MW halo is mildly radial (Deason et al 2011). Furthermore, values of b < -1 are known to be unrealistic velocity anisotropies for distant halo stars (e.g., Deason et al 2013;Cunningham et al 2016). Taking all of this information into account, we set a conservative lower limit of b = -0.5 lower .…”
Section: Priorsmentioning
confidence: 99%
“…On the other hand, there is strong evidence to expect  b 0 for the Galactic stellar halo (Kafle et al 2014), and previous studies have shown that the velocity distribution of GCs in the MW halo is mildly radial (Deason et al 2011). Furthermore, values of b < -1 are known to be unrealistic velocity anisotropies for distant halo stars (e.g., Deason et al 2013;Cunningham et al 2016). Taking all of this information into account, we set a conservative lower limit of b = -0.5 lower .…”
Section: Priorsmentioning
confidence: 99%
“…As a result, a considerable effort has been expended in measuring the stellar halo's kinematic moments (e.g., Xue et al 2008;Bond et al 2010;Cunningham et al 2016). Recently, emphasis has been placed on the measurement of the velocity anisotropy parameter (β), the ratio of tangential to radial random motion, which is expected to be positive from simple numerical experiments on halo formation (Binney & Tremaine 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, emphasis has been placed on the measurement of the velocity anisotropy parameter (β), the ratio of tangential to radial random motion, which is expected to be positive from simple numerical experiments on halo formation (Binney & Tremaine 2008). However, measurements of β in the MW have suggested that it is negative within 15 R/kpc25 (see Kafle et al 2012, King et al 2015, but see Deason et al 2013b, Cunningham et al 2016 for alternative values), leading to speculation that the exact merger and dissipation history of the stellar halo could strongly affect its velocity anisotropy profile (Deason et al 2013a(Deason et al , 2013b. In spite of these recent efforts to infer the MW's accretion history from measurements of the density profile and β, there have been no systematic studies of how β varies with radius in realistic cosmological hydrodynamic simulations that demonstrate that β is in fact a tracer of assembly history.…”
Section: Introductionmentioning
confidence: 99%
“…In Deason et al (2013b), we published the first proper motions of distant Milky Way halo stars; in Cunningham et al (2016), we present the line-of-sight (LOS) velocities for those same stars. Our 13 objects are the first stars outside of the solar neighborhood to have 3D kinematic information.…”
mentioning
confidence: 99%
“…Using the 6D phase space information from our survey, we have made the first direct measure of the velocity anisotropy outside of the solar neighborhood (Cunningham et al 2016).…”
mentioning
confidence: 99%